Análise da precisão de um sistema de navegação óptica para cirurgia assistida em implantodontia: resultados preliminares - Milki Neto, João (2011)
The aim of this study is to test the accuracy of a surgical navigator with a optical tracking system and the equipment used was the Eximius (Artis, Brasília-DF, Brazil) which is a nation navigator and if this system allows the clinical use for dental implant placement. A cube with symmetrical references on each face was built in a computer program and then prototyped with a nylon type Technyl® (poliamida 6.6, Rhodia, São Paulo, Brazil). Then a tomography of the cube was done in a multi slice, high resolution equipment (General Electric, EUA 2001). The tomography data was taken to the navigator and the fiducial registration error was done in order to fuse the virtual cube to the real cube in to the Eximius program (Artis, Brasília-DF, Brazil). Were tested three different manners of calibration, linear, planar and volumetric on three selected faces of the cube. Two examiners trained and qualified made two diferente calibration for each type of geometrical calibration tested using 6 points in each face of the cube. After registered the calibration error it was recorded the target registration error twice in 56 points on the three faces of the cube. The data was then analyzed. The results show that the planar and volumetric calibrations had good results, but the most acquired was the volumetric which varied between 0.20 to a 1.70mm (MD 0.91mm e DP 0.35mm). The navigator is much precise and allows us to clinical use in implantodonty, but more studies are required to improve this technology.